The Etiology of Auditory Hallucinations in Schizophrenia: From Multidimensional Levels - Shao, Xu; Liao, Yanhui; Gu, Lin; Chen, Wei; Tang, Jinsong (Frontiers in Neuroscience, 2021)
Enormous efforts have been made to unveil the etiology of auditory hallucinations, and multiple genetic and neural factors have already been shown to have their own roles. Previous studies have shown that auditory hallucinations in schizophrenia vary from those in other disorders, suggesting that they have unique features and possibly distinguishable mechanisms worthy of further investigation. In this review, we intend to offer a comprehensive summary of current findings related to auditory hallucinations in schizophrenia from aspects of genetics and transcriptome, neurophysiology (neurometabolic and electroencephalogram studies), and neuroimaging (structural and functional magnetic resonance imaging studies, and transcriptome-neuroimaging association study). Main findings include gene polymorphisms, glutamate level change, electroencephalographic alterations, and abnormalities of white matter fasciculi, cortical structure and cerebral activities especially in multiple regions including auditory and language networks. More solid and comparable research is needed to replicate and integrate ongoing findings from multidimensional levels.